2002
DOI: 10.1021/np010434n
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Glycosides and Oligosaccharide Multiesters from the Roots of Polygala dalmaisiana

Abstract: Four new polyphenolic glycosides, dalmaisiones A-D (1-4), 16 new oligosaccharide multiesters, dalmaisioses A-P (5, 7-21), and one known tetrasaccharide multiester, reiniose G (6), were isolated from the roots of Polygala dalmaisiana. The structures of the new compounds were elucidated on the basis of chemical and spectroscopic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Moreover, the present methodology was used for the structural revision of two natural products, ( Z )-4’-chloroaurone 30 [ 64 ], and ( Z )-2’-hydroxyaurone 32 [ 65 ], proving that the assumed structures were not the correct ones. Thus, flavonoid systems 30 and 32 could be prepared by the above three step strategy which revealed that their spectral data did not match with the previously reported data of the natural isolated ones.…”
Section: Cycloisomerization Processes Involving Carbon-heteroatom mentioning
confidence: 99%
“…Moreover, the present methodology was used for the structural revision of two natural products, ( Z )-4’-chloroaurone 30 [ 64 ], and ( Z )-2’-hydroxyaurone 32 [ 65 ], proving that the assumed structures were not the correct ones. Thus, flavonoid systems 30 and 32 could be prepared by the above three step strategy which revealed that their spectral data did not match with the previously reported data of the natural isolated ones.…”
Section: Cycloisomerization Processes Involving Carbon-heteroatom mentioning
confidence: 99%
“…A number of investigations had been carried out to identify the compounds responsible of the biological activity of Yuan zhi [ 1 , 2 , 3 , 4 ]. Some phenylpropenoyl sucroses from Yuan zhi became hot research topics because of their bioactivity of preventing memory disorders [ 5 , 6 , 7 , 8 ]. The understanding and diagnosis of many diseases mainly relies on the metabolic profiling of biological fluids such as urine and plasma, as their compositions reflect the biochemical status of a living organism and imply information about the biological processes associated with pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Further comparison with previous NMR data confirmed that this moiety is a b-D-glucoside. 8,9 The NOESY spectra showed that H-1 0 was correlated with H-3 0 (d H 3.36) and H-5 0 (d H 3.37), thereby proving the configuration of b-D-glucoside. The HMBC correlation of the anomeric proton H-1 0 (d H 4.26) with C-18 (d C 88.8) and C-20 (d C 57.8) established the glucosidic linkage at position N-19.…”
Section: Resultsmentioning
confidence: 91%